Análisis de la posesión notoria del estado de hijo en la Legislación ecuatoriana y sus efectos jurídicos - Defaz Cadena, María Dolores (2023)
The general objective was to examine the notorious possession of the status of son in Ecuador, by reviewing its concept and its legal requirements. The specific objectives were: 1.- describe the national legislation pertinent to the processing of the notorious possession of the status of son in the legal context of Ecuador\; 2.- determine compliance with current regulations in the processing of notorious possession of the status of child in the Ecuadorian legal field\; 3.- Analyze the contributions of the national doctrine. The focus of this research was qualitative documentary, socio-legal, deductive method for the search for information within legal bases from an instrument such as the interview. The conclusions are underlinedthat: it is considered as a means of proof to be able to establish the filiation, in otherwords, the relationship of kinship between people, in this case between an alleged father or mother and a child, whether minor or adult. The organization of the regulations is the Constitution of the Republic, the Civil Code and the COGEP.